KEGIATAN KELOMPOK MUSIK PENGIRING GEREJA KRISTEN PROTESTAN SIMALUNGUN YOGYAKARTA - JOST DKLAR SARAGIH (Saraswati)
Accompaniment Music Group Activities of Gereja Kristen ProtestanSimalungun, firstly been implemented with the simple music instruments, that isusing by keyboard instrument. This activities in the sense of need to increase forcomplicated with the other instrument so that produce ensemble of liturgy musicaccompaniment. This research using by qualitative method, musicologist. Thisresearch considered creative and effective because the players able toaccompaniment with the songs very well, and congregations find it in worship.Keywords: Music of Church, Congregations, Accompaniment Music Group.